Analisis Hukum Islam terhadap Keabsahan Jual Beli Kendaraan Bermotor tanpa STNK - Dewanty, Megananda Aruna; Muh. Solihuddin (Program Studi Hukum Ekonomi Syariah (Muamalah), 2024)
This research was conducted to find out how the validity of buying and selling motorcycles without Vehicle Number Certificate (STNK) according to Islamic law, especially with the right to khiyar. The method used in this study is a literature study method, through a descriptive approach. The results of the study show that the purchase of a motorcycle without the (STNK) that is already known by both parties and proven without a stolen motorcycle, then according to Islamic law the transaction is considered legal. The transaction has fulfilled the principles and conditions of buying and selling as well as the existence of khiyar rights given to buyers, namely khiyar adis and khiyar conditions to prevent problems in the future. However, judging from the positive law, the sale and purchase are void because it does not follow the Traffic Law. In the context of buying and selling motor vehicles without STNK, it is important to check the documents and legality of the vehicle's condition so as not to violate the principle of fairness in buying and selling. Therefore, the feasibility of this kind of transaction must be carefully considered, as well as ensuring that the seller confirms to the buyer and understands the right of khiyar to protect the buyer if there are problems in the future.